2022
DOI: 10.3390/jpm12020288
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Association of Genetically Predicted Neuroticism with Coronary Artery Disease: A Two-Sample Mendelian Randomization Study

Abstract: Background: Observational studies on the association between neuroticism and coronary artery disease (CAD) are still rare, and the results of existing studies are not consistent. The present study aimed to explore causal associations of neuroticism with CAD. Methods: The summary-level data of GWAS for neuroticism and 12 items used to assess neuroticism were extracted from the UK Biobank, and included up to 380,506 participants. The general data for CAD were obtained from the CARDIoGRAMplusC4D consortium, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…For example, neuroticism scores did not show a causal genetic association with coronary artery disease. 34 However, the genetic liability of depression is associated with a higher risk of coronary artery disease and myocardial infarction. 35 Individuals with higher levels of neuroticism also showed an increased risk of heart failure and myocardial infarction in another MR study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neuroticism scores did not show a causal genetic association with coronary artery disease. 34 However, the genetic liability of depression is associated with a higher risk of coronary artery disease and myocardial infarction. 35 Individuals with higher levels of neuroticism also showed an increased risk of heart failure and myocardial infarction in another MR study.…”
Section: Discussionmentioning
confidence: 99%
“…So far there is limited evidence from MR studies evaluating association between personality traits and CVD with mixed results. A recent MR study using instrumental variable for neuroticism comprised of 27 SNPs found causal association between neuroticism score and atrial fibrillation (Sun et al, 2021) while another MR study found no association between genetically predicted neuroticism score and coronary artery disease (Yan et al, 2022). However, in the MR analyses of individual neuroticism items, mood swings were found to genetically increase the risk of coronary artery disease (Yan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A recent MR study using instrumental variable for neuroticism comprised of 27 SNPs found causal association between neuroticism score and atrial fibrillation (Sun et al, 2021) while another MR study found no association between genetically predicted neuroticism score and coronary artery disease (Yan et al, 2022). However, in the MR analyses of individual neuroticism items, mood swings were found to genetically increase the risk of coronary artery disease (Yan et al, 2022). MR analyses have also indicated the direction of causal effects from neuroticism to CVD, but not the reverse (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%